1998
DOI: 10.1152/ajplung.1998.275.2.l303
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression and localization of 5-lipoxygenase accompany macrophage differentiation in the lung

Abstract: The alveolar macrophage (AM) exhibits a greater capacity to synthesize bioactive leukotrienes from arachidonic acid than does its circulating precursor the peripheral blood monocyte. Macrophage differentiation in the lung entails cellular residence within both the pulmonary interstitial and alveolar compartments. In the present study, we sought to determine 1) whether this enhanced metabolic activity was acquired during maturation within the alveolar space and 2) the underlying mechanisms responsible for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Preliminary experiments checked the cross-reactivity of the used antibodies against respective LOX antigens with lung (ALOX5 and -12) and spleen (ALOX12) positive controls. As was consistent with the previously reported results (Maruyama et al 1989, Covin et al 1998, Kawajiri et al 2000, alveolar epithelial cells in the lung and white pulp in the spleen of adult rats showed positive immunoreaction for respective antigen (data not shown).…”
Section: Distribution Of Immunoreactive Lox Isoforms In the Preovulatsupporting
confidence: 93%
See 1 more Smart Citation
“…Preliminary experiments checked the cross-reactivity of the used antibodies against respective LOX antigens with lung (ALOX5 and -12) and spleen (ALOX12) positive controls. As was consistent with the previously reported results (Maruyama et al 1989, Covin et al 1998, Kawajiri et al 2000, alveolar epithelial cells in the lung and white pulp in the spleen of adult rats showed positive immunoreaction for respective antigen (data not shown).…”
Section: Distribution Of Immunoreactive Lox Isoforms In the Preovulatsupporting
confidence: 93%
“…This experiment was also carried out for three different samples at each time point. Sections of lung and spleen of adult rats served as positive controls for ALOX5 (lung) and ALOX12 (lung and spleen) immunohistochemistry (Maruyama et al 1989, Covin et al 1998, Kawajiri et al 2000.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…This has been demonstrated in primary cells, such as neutrophils (33) and macrophages (53), as well as in molecular model systems, such as transfected NIH 3T3 cells (34). In addition, we have previously demonstrated that impairment of nuclear import of 5-LO, achieved by selectively inactivating a nuclear import sequence, reduces LTB 4 synthesis by more than 60% (34).…”
Section: Discussionmentioning
confidence: 82%
“…1). 5-LPO activity requires perinuclear translocation from the cytosol (9) and association with FLAP homodimer (7,27,39) and is increased by phosphorylation at serine 271 (55). LTB 4 and cysLTs exert their actions by binding to distinct G proteincoupled receptors: BLT1 and BLT2 for LTB 4 , and cysLT 1 and 2 receptors (cysLT 1 R and cysLT 2 R) for cysLTs ( Fig.…”
mentioning
confidence: 99%